2020
DOI: 10.3390/environments7090065
|View full text |Cite
|
Sign up to set email alerts
|

Continuous OTM 33A Analysis of Controlled Releases of Methane with Various Time Periods, Data Rates and Wind Filters

Abstract: Other test method (OTM) 33A has been used to quantify emissions from natural gas sites since it was introduced by the Environmental Protection Agency (EPA). The method relies on point source Gaussian (PSG) assumptions to estimate emissions rates from a targeted site or source. However, the method often results in low accuracy (typically ±70%, even under conducive conditions). These accuracies were verified with controlled-release experiments. Typically, controlled releases were performed for short periods (15–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The Gaussian point source method, OTM33A issued by the U.S. Environmental Protection Agency, is used to calculate the methane emission rate. Usually 20 min concentration measurement is required to acquire an emission rate estimation 12 . In our study, the measurement time is between 2 and 7 h. Hence in our analysis, we break down the whole measuring period to several sequential 20 min sections, and data within each section is analyzed to obtain an average emission rate within that section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gaussian point source method, OTM33A issued by the U.S. Environmental Protection Agency, is used to calculate the methane emission rate. Usually 20 min concentration measurement is required to acquire an emission rate estimation 12 . In our study, the measurement time is between 2 and 7 h. Hence in our analysis, we break down the whole measuring period to several sequential 20 min sections, and data within each section is analyzed to obtain an average emission rate within that section.…”
Section: Resultsmentioning
confidence: 99%
“…Their capacity and configurations were listed in Table 1 . The following factors were considered when selecting these stations for effective application of OTM 33A method in the EPA official website, which are used as the main basis for the selection of LNG fueling stations 11 , 12 . An accessible and safe downwind site for instrument installation; A relatively consistent wind condition blowing from the source to the point of measurement; Zero or few obstructions between the source and the measurement point; No other nearby emission sources.…”
Section: Instrument and Emission Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the distance between the measuring position and the objective has to be clearly known, and there are no other nearby emission sources besides the target source. Fourth, the emission source has to located close to the ground [18,98,99]. There are three important parameters in OTM33a models: meteorological parameters, position information, and methane concentration.…”
Section: Otm33a Methodsmentioning
confidence: 99%
“…Heltzel et al [99] pointed out that the uncertainty of an uncontrolled OTM33a method can reach ±70%. In order to solve this problem, Heltzel et al used controlled release experiments to explore the effect of sampling frequency, sampling time, selected wind direction range, and other factors on the uncertainty of the estimation result [99]. They found that the above factors had a significant impact on the accuracy of the OTM33a method.…”
Section: Otm33a Methodsmentioning
confidence: 99%